Different prognostic associations of beta-blockers and diuretics in heart failure with preserved ejection fraction with versus without high blood pressure. Issue 3 (March 2019) - Matsushita, Kenichi; Harada, Kazumasa; Miyazaki, Tetsuro; Miyamoto, Takamichi; Kohsaka, Shun; Iida, Kiyoshi; Tanimoto, Shuzou; Takei, Makoto; Hosoda, Toru; Yamamoto, Yoshiya; Shiraishi, Yasuyuki; Yoshino, Hideaki; et al.
Abstract : Objective: No agents have been proven to improve survival in heart failure with preserved ejection fraction (HFpEF), but the phenotypic diversity of HFpEF suggests it may be possible to identify specific HFpEF phenotypes that will benefit from certain treatments. This study compared the risk factors for and prognostic impacts of treatments on in-hospital mortality between HFpEF patients with (+) and without (–) high blood pressure (HBP). Methods: Data on 2238 consecutive HFpEF patients were extracted from Tokyo CCU Network data registry and analysed. HFpEF was defined as an ejection fraction greater than or equal to 50%; HBP was defined as elevated systolic blood pressure (>140 mmHg) at admission. Potential risk factors for in-hospital mortality were selected by univariate analyses and those with P  < 0.10 were used in multivariate Cox regression analysis with forward selection (likelihood ratio) to identify significant factors. Results: In-hospital mortality was significantly lower for HFpEF + HBP than HFpEF – HBP patients (log-rank, P  < 0.001). Independent risk factors for in-hospital mortality in HFpEF + HBP patients were older age (hazard ratio 1.069) and in-hospital treatment without beta-blockers (hazard ratio 7.946), whereas older age (hazard ratio 1.035), higher C-reactive protein (hazard ratio 1.047), higher B-type natriuretic peptide (hazard ratio 1.000) and in-hospital treatment without diuretics (hazard ratio 4.201) were identified as independent risk factors in HFpEF – HBP patients. Conclusion: There were significant differences in prognostic factors, including beta-blocker and diuretic treatments, for in-hospital mortality between HFpEF patients with and without HBP. These findings suggest possible individualized therapies for patients with HFpEF. Abstract : Supplemental Digital Content is available in the text